Evaporation-induced self-assembly of gold nanorods on a hydrophobic substrate for surface enhanced Raman spectroscopy applications - Usman, Muhammad; Ishafaq, M. U. U.; Muhammad, Zahir; Ali, Wajid; Dastgeer, Ghulam; Zhang, Xiao; Wang, Liang (Frontiers in Materials, 2023)
The controllable assembly of plasmonic nanoparticles has emerged as one of the most important approaches for surface enhanced Raman spectroscopy (SERS) applications. This study developed a simple method to fabricate a large-scale ordered assembly of gold nanorods (GNRs) by controlling the droplet evaporation mode on hydrophobic substrates. The hydrophobic substrates were fabricated in a very efficient and cost-effective way by simply spin coating the silicone oil followed by annealing. The analyte molecule rhodamine 6G (R6G) was used as surface-enhanced Raman scattering probes to demonstrate the potential effects of the synthesized arrays. The hydrophobic substrates platform allows for the enrichment and delivery of analyte molecules into the SERS sensitive site due to the suppression of the coffee ring effect caused by the smooth contraction motion of the base contact radius of the droplet without any pinning. Thus, the homogeneous distribution of abundant SERS hotspots inside the self-assembly reproducibly SERS signal. This new approach could lead to diverse packing structures and functions by varying guest nanoparticles in the suspensions.